La inclusión constructiva a la sociedad como factor de análisis, ante las infracciones cometidas por adolescentes en el Ecuador - Segundo Vladimir, Pucha Sandal (2021)
ABSTRACT This research is based mainly on studying the norms and rules of the criminal system of juvenile offenders in Ecuador. In this sense, the topic deals with "CONSTRUCTIVE INCLUSION TO SOCIETY AS AN ANALYSIS FACTOR, IN THE FACE OF INFRACTIONS COMMITTED BY ADOLESCENTS IN ECUADOR." Therefore, the Norms of the Organic Code of Children and Adolescents are analyzed, specifically, the aspects of the offenses committed by adolescent transgressors, the Constitution of the Republic of Ecuador, international treaties and norms, exclusively the International Convention on the rights of children. In conclusion, despite the extensive study of the norm and jurisprudence, we will focus on an axis that allows us to protect the rights of the youth and make the best interests of the child prevail. It is necessary to adapt the liability regime for adolescent offenders in Ecuador. Consequently, this work constitutes a simultaneous study of the different measures and rules applicable to adolescent offenders. This study is based on the search for new alternatives or measures to safeguard the rights of children and adolescents. The study also focused on applying the law in the case of disobedience to ensure that the sanction imposed is framed within respect of these rights and safeguarding the rights of youth. KEY WORDS: Higher Interest of the Child, Adolescent Offenders, Constructive Inclusion Reviewed by: Msc. Adriana Cundar Ruano, Ph, D. ENGLISH PROFESSOR c.c. 1709268534